Pengaruh Model Cooperative Learning Tipe Picture And Picture Terhadap Kemampuan Membaca Permulaan Pada Siswa Kelas 1 Sekolah Dasar - Siti Masitoh; Anggy Giri Prawiyogi (LPPM Universitas Buana Perjungan Karawang, 2020)
This study aims to determine the difference in the effect on the ability to read the beginning by using Model Coopertive Learning Type of picture and picture in grade 1 SDN Sukapura III. This type of research is Experimentation. The design used in this study is Nonequivalent Control Group Design.The population used in this study were all students of SDN Sukapura III. The sample used was class 1 SDN Sukapura III, amounting to 50 students, where class 1 A numbered 25 students as Experiment class and class 1 B amounted to 25 students as control class. Data collection techniques used in this study were in the form of a preliminary reading test using five indicators, namely the accuracy of writing the sound, the reasonableness of pronunciation, the reasonableness of intonation, fluency, sound clarity. Test instruments used to determine the ability to read the beginning is to use an oral test or pratik reading the beginning. This test consists of an initial test (pretest) and a testpost-action (posttest). The results of the study showed Pretest the average value of the experimental class was 50.24 and the control class was 51.04. After treatment of learning using the Cooperative Learning Model Type Picture and Picture, the results of data analysis in the experimental class Postest with an average of 86.24 and the value of the control class with an average of 70.88. Based on the hypothesis test shows that the significant value is 0,000. Due to the significant value of 0.000 < α = 0.05, then H 0 accepted, meaning that this proves that there is a difference between the Model Cooperative Learning mode Picture and picture of the ability to read beginning in grade 1 to grade not use the Model Cooperative Learning mode Picture and picture. From the results empirically that it can be concluded sump wa there are differences in the effect of M odel Cooperative Learning Type of picture and picture of the ability to read beginning in grade 1 SDN Sukapura III 2018/2019 academic year.